LARVICIDAL EFFICACY OF LEAF EXTRACTS OF Rhanterium epapposum Oliv. AGAINST DENGUE FEVER MOSQUITO VECTOR LARVAE, Aedes aegypti L., (DIPTERA: CULICIDAE) (Applied Biological Research, 2023)
Dengue fever, transmitted by Aedes aegypti L. (Diptera: Culicidae), is the  most important disease affecting human health and economy in the  western part of Saudi Arabia. This study aimed to investigate the  larvicidal activities of ethanolic, acetonic and aqueous extracts prepared  from the leaves of Arfaj (Rhanterium epapposum Oliv.) against dengue  fevemosquito vector, Aedes aegypti, under laboratory conditions. The  larvicidal potency ofethanolic extract at high concentration of 50000 ppm  was up to 98% after 24 h exposure. In contrast, acetonic and aqueous  extracts caused 72 and 30% larval mortality, respectively, at the same  concentration and exposure time. After 48 h exposure, the mortalities  increased by 99, 86 and 35%, respectively, for ethanolic, acetonic and  aqueous extracts. This study showed that the ethanolic extract had a  higher larvicidal effect with lower LC50 value (168.15 ppm), followed by acetone (847.75 ppm) and aqueous (2278.22 ppm) extracts after 24 h  exposure. Further studies are needed to isolate and identify the primary  component responsible for larvicidal efficiencyof this plant extract which  may give good insights for developing a sustainable mosquito control  method.
Keywords: Botanical pesticides; dengue fever vector; ethanolic extract; mosquito control; Rhanterium epapposum